2021
DOI: 10.3390/molecules26164770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Distillation Time on the Chemical Composition, Antioxidant Potential and Antimicrobial Activity of Essential Oils from Different Cannabis sativa L. Cultivars

Abstract: Within the unavoidable variability of various origins in the characteristics of essential oils, the aim of this study was to evaluate the effect of the distillation time on the chemical composition and biological activity of Cannabis sativa essential oils (EOs). The dry inflorescences came from Carmagnola, Kompolti, Futura 75, Gran Sasso Kush and Carmagnola Lemon varieties from Abruzzo region (Central Italy), the last two being new cultivar here described for the first time. EOs were collected at 2 h and 4 h o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
3
23
0
1
Order By: Relevance
“…Regarding Lemon Conti Kush, Fresh Mountain, and Amnesia Cookies, originated by the Kompolti variety, a considerable abundance of myrcene and other monoterpenes was detected in their EOs. This was in accordance with some literature findings in which the Kompolti EO from dried inflorescences appeared to be richer in the same compounds, rather than in sesquiterpenes [ 45 ]. So, it could be deduced that such differences in the distribution of mono- and sesquiterpenes in hemp EOs seem to be dependent on the extraction method and plant material status.…”
Section: Resultssupporting
confidence: 93%
“…Regarding Lemon Conti Kush, Fresh Mountain, and Amnesia Cookies, originated by the Kompolti variety, a considerable abundance of myrcene and other monoterpenes was detected in their EOs. This was in accordance with some literature findings in which the Kompolti EO from dried inflorescences appeared to be richer in the same compounds, rather than in sesquiterpenes [ 45 ]. So, it could be deduced that such differences in the distribution of mono- and sesquiterpenes in hemp EOs seem to be dependent on the extraction method and plant material status.…”
Section: Resultssupporting
confidence: 93%
“…Palmieri et al [72] studied the variability of Cannabis essential oils from various origins and observed that the time of distillation affected the chemical composition of terpenic components, sesquiterpenes, and CBD with consequent variations in the anti-microbial activities against Staphylococcus aureus, Listeria monocytogenes, and Enterococcus faecium. Zheljazkov et al [73] compared the anti-microbial activity of nine wild hemp (Cannabis sativa spp.…”
Section: Anti-microbial Activity Of Essential Oils From Cannabis Sati...mentioning
confidence: 99%
“…The Cannabis sativa L. plants produce more than 560 chemicals, including at least 144 cannabinoids and 200 terpenoids, as well as flavonoids and polyunsaturated fatty acids [15,33,34,42,63,67,72,73,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107]. The most common phytocannabinoids are ∆ 9 -tetrahy drocannabinol (∆ 9 -THC) and cannabidiol (CBD), which are the neutral homologs of tetrahydrocannabinolic acid (THCA) and cannabidiol acid (CBDA), respectively [108].…”
Section: Phytocannabinoidsmentioning
confidence: 99%
“…rapa DC.) [23] Pseudomonas fluorescens 4 Lavandula × intermedia [18]; Origanum heracleoticum and O. majorana [30]; Cannabis sativa [117] Pasteurella multocida 1 Morus alba [26] Among the plants effective against Gram+ bacteria, the major number of described species (39) was recorded for S. aureus (29%, Figure 1a), and, among these, four were specifically recorded as being effective against the MSSA strain. Twelve contributions (9%) were recorded for plants effective against S. epidermidis, 17 (13%) against B. cereus, and 21 (16%) against Listeria monocytogenes.…”
Section: Klebsiella Pneumoniae 16mentioning
confidence: 99%